Non-contact multi-particle annular patterning and manipulation with ultrasound microbeam - Lee, Changyang (American Institute of Physics, 2014)
Multiparticle-trapping offers diverse opportunities and applications in biotechnology. It can be applied to creating various functional materials or organizing reactive particles. In this paper, we demonstrate that it is possible to trap and manipulate multi-particles in an annular pattern with a 24 MHz focused ring-type single element ultrasound transducer. Acoustic ring trap can be useful in undertaking biotropism studies due to an equal-distance condition from the center. Also, this ring trap could serve as a force shield to protect analysis area from other cells. The experimental results showed the capability of the proposed method as a multi-cell manipulator in formatting specific patterns of small cells like sperms.